CAN MOBILITY AFFECT GRAMMAR AT THE MORPHOSYNTACTIC LEVEL? A STUDY IN BRAZILIAN PORTUGUESE - Siqueira, Manoel; Freitag, Raquel Meister Ko. (Organon, 2022)
In this paper, a study about the presence of the definite article before possessed NP (D-presence) in Brazilian Portuguese is carried out with a sample constituted by sociolinguistic interviews with students from the Federal University of Sergipe (UFS), Brazil, to observe whether the distribution pattern of the variable suggests an effect of mobility in the students’ speech. An analysis is carried out with a sample from the Deslocamentos 2020 dataset, composed of sociolinguistic interviews with college students from Universidade Federal de Sergipe (UFS), balanced for degree of mobility (students from Sergipe, Alagoas, and Bahia), time in the undergraduate program, and sex (n = 60). Results show that D-presence is sensitive to dialectal factor, with D-absence predominating in data from Sergipe and Alagoas, and D-presence predominating in data from Bahia, but it is not sensitive to the integration into the new community considering speakers’ time in the undergraduate program. This result contributes to revealing how mobility affects grammar at the morphosyntactic level.